Sunlight assisted degradation of dye molecules and reduction of toxic Cr(VI) in aqueous medium using magnetically recoverable Fe3O4/reduced graphene oxide nanocomposite - Boruah, Purna K.; Borthakur, Priyakshree; Darabdhara, Gitashree; Kamaja, Chaitanya Krishna; Karbhal, Indrapal; Shelke, Manjusha V.; Phukan, Pallabi; Saikia, Dulen; Das, Manash R. (RSC Advances, 2016)
In view of the significant impact of magnetically recoverable catalysts in photocatalytic applications, Fe3O4/reduced graphene oxide (rGO) nanocomposite photocatalyst was synthesized by adopting an eco-friendly solution chemistry approach and has been characterized by high resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy and photoluminescence (PL) spectroscopy. Fe3O4/rGO nanocomposite is efficiently utilized towards photocatalytic degradation of carcinogenic and mutagenic cationic as well as anionic dye molecules namely methyl green (MG), methyl blue (MB) and rhodamine B (RhB) under direct sunlight irradiation. The Fe3O4/rGO nanocomposite also demonstrated excellent photocatalytic reduction of aqueous Cr(VI) solution to nontoxic aqueous Cr(III) solution of more than 96% within 25 min under sunlight irradiation. Moreover, reusability of the magnetically recovered photocatalyst was studied efficiently up to 10 cycles in the degradation process. The catalyst was also characterized after the degradation of the dye molecule and the particle size of the Fe3O4 nanoparticles on the rGO sheets remained unchanged. The present investigation focuses on the importance of the use of Fe3O4/rGO nanocomposite towards photocatalytic degradation of waste water containing organic dye pollutants and toxic Cr(VI), as an easily recoverable and reusable photocatalyst with potential for many environmental remediation applications.

Synthesis of novel Cu2S nanohusks as high performance counter electrode for CdS/CdSe sensitized solar cell - Kamaja, Chaitanya Krishna; Devarapalli, Rami Reddy; Dave, Yasha; Debgupta, Joyashish; Shelke, Manjusha V. (Journal of Power Sources, 2016)
An important component of quantum dot sensitized solar cells (QDSSC) is the counter electrode which mediates the regeneration of oxidized quantum dots by reducing the polysulphide electrolyte. However, design and synthesis of an efficient counter electrode material is a challenging task. Herein, we report the synthesis of a unique Cu2S nanohusks directly on FTO coated glass substrates by electrodeposition and used as a counter electrode in QDSSC. When these electrodes are used for the reduction of polysulfide electrolyte in QDSSC, they exhibit higher catalytic activity and photovoltaic performance as compared to the Platinum counter electrode. The power conversion efficiency of about 4.68% has been achieved by optimizing the deposition time of Cu2S. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: counter electrode; Cu2S electrodeposition; Cu2S nanohusks; Quantum dot-sensitized solar cell